Epidemiological Characteristics and Mortality Predictors in Patients Over 70 Years Submitted to Coronary Artery Bypass Grafting - Kaufman,Renato (2018)
Abstract Background: Coronary artery disease is the leading cause of death worldwide, with age being an independent risk factor for mortality in patients submitted to surgical revascularization. Objective: To evaluate the mortality risk predictors in patients older than 70 years submitted to myocardial revascularization. Methods: This is a retrospective cohort study of a cardiac surgery database. Logistic regression was used to assess independent death predictors. Results: A total of 372 patients submitted to surgical revascularization from 2004 to 2012 were assessed. The main cardiovascular risk factor was hypertension, followed by diabetes mellitus. Mortality at 30 days was 19.35%. The presence of peripheral vascular disease (OR: 2,47), emergency surgery (OR: 4,86) and combined valve procedure (OR: 3,86) were independent predictors of death. Conclusion: The surgical procedure in elderly patients showed a higher mortality than in the general population. Peripheral vascular disease, emergency surgery and combined valve procedures increased the risk of death in these patients.